2021
DOI: 10.18251/ijme.v23i1.2103
|View full text |Cite
|
Sign up to set email alerts
|

Rendering Latinas Invisible: The Underrepresentation of Latinas in K-12 History

Abstract: There is a lack of research on the prevalence of Latinas in K-12 history textbooks. This research offers a content analysis of the unique gendered contributions of Latinas in history to fulfill this gap in educational research. Twelve middle and high school textbooks were examined using content analysis to assess the extent of Latina inclusion in history as well as how Latinas were characterized when discussed in books. The author confirms that there is an underrepresentation of Latinas in history textbooks. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Fung and Chung (2021) stated that the role model parent response is important in the selfregulation development of preschool children. There are many studies in the literature proving that role models are especially effective in the development of children's self-regulation (Acar et al, 2022;Augustine et al, 2022;Broda et al, 2020;Cai et al, 2022;Fung & Chung, 2021;Karaca & Bektas, 2021;Kurtovic et al, 2021;Lenes et al, 2020;Lerner et al, 2021;Leslie, 2021;Ringoot et al, 2021;Vitiello et al, 2022;Xie & Li, 2022;Zieli'nska et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fung and Chung (2021) stated that the role model parent response is important in the selfregulation development of preschool children. There are many studies in the literature proving that role models are especially effective in the development of children's self-regulation (Acar et al, 2022;Augustine et al, 2022;Broda et al, 2020;Cai et al, 2022;Fung & Chung, 2021;Karaca & Bektas, 2021;Kurtovic et al, 2021;Lenes et al, 2020;Lerner et al, 2021;Leslie, 2021;Ringoot et al, 2021;Vitiello et al, 2022;Xie & Li, 2022;Zieli'nska et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of this study is to reveal the importance of role models in meeting this need. There are field studies examining the role model and selfregulation together (Acar et al, 2022;Augustine et al, 2022;Cai et al, 2022;Fung & Chung, 2021;Karaca & Bektas, 2021;Kurtoviç et al, 2021;Leslie, 2021;Ringoot et al, 2021;Vitiello et al, 2022;Xie & Li, 2022;Zielinska et al, 2022). Augustine et al (2022) showed that family adjustment behavior enriched with self-regulation helps reduce anxiety problems.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals who develop self‐regulation skills can acquire important cognitive and affective features from the right role models (Mueller et al, 2011; Urban et al, 2010). Similar to the model we developed, many studies have proven role models to be important for individuals about developing self‐regulation skills (Acar et al, 2022; Augustine et al, 2022; Broda et al, 2020; Cai et al, 2022; Fung & Chung, 2021; Karaca & Bektas, 2021; Kurtovic et al, 2021; Lenes et al, 2020; Leslie, 2021; Ringoot et al, 2021; Vitiello et al, 2022; Xie & Li, 2022; Zielińska et al, 2022). These studies were mostly conducted with children.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…| 3569 help and emotional support, as these have the potential to positively and negatively impact academic resilience. Leslie (2021) argued that all students must look at the culturally relevant role models represented in textbooks for a more inclusive and engaging classroom experience. Özbalci et al (2021) study revealed that half of the 16 students with special needs who participated in the activity were interested in the role model's profession and exhibited entrepreneurial skills for receiving on-the-job training appropriate to their needs.…”
Section: Role Modelmentioning
confidence: 99%
“…For instance, all women are often underrepresented in portrayals in textbooks and other education materials compared to men, yet, women of color may be even more underrepresented than White women, as education materials may reflect disparities seen in organizations. A content analysis of 12 middle and high school US textbooks used in two of the largest US states supports this notion (Leslie, 2021). They found that Latinas and Asian women were represented less than 1% across all materials, 2% of figures mentioned were Black women, and 10% were White women.…”
Section: Integrating Leadership Self-efficacy and Intersectionalitymentioning
confidence: 94%